Gabapentin Modulates HCN4 Channel Voltage-Dependence - Tae, Han-Shen; Smith, Kelly M.; Phillips, A. Marie; Boyle, Kieran A.; Li, Melody; Forster, Ian C.; Hatch, Robert J.; Richardson, Robert; Hughes, David I.; Graham, Brett A.; Petrou, Steven; Reid, Christopher A. (Frontiers in Pharmacology, 2017)
Gabapentin (GBP) is widely used to treat epilepsy and neuropathic pain. There is evidence that GBP can act on hyperpolarization-activated cation (HCN) channel-mediated Ih in brain slice experiments. However, evidence showing that GBP directly modulates HCN channels is lacking. The effect of GBP was tested using two-electrode voltage clamp recordings from human HCN1, HCN2, and HCN4 channels expressed in Xenopus oocytes. Whole-cell recordings were also made from mouse spinal cord slices targeting either parvalbumin positive (PV+) or calretinin positive (CR+) inhibitory neurons. The effect of GBP on Ih was measured in each inhibitory neuron population. HCN4 expression was assessed in the spinal cord using immunohistochemistry. When applied to HCN4 channels, GBP (100 μM) caused a hyperpolarizing shift in the voltage of half activation (V1/2) thereby reducing the currents. Gabapentin had no impact on the V1/2 of HCN1 or HCN2 channels. There was a robust increase in the time to half activation for HCN4 channels with only a small increase noted for HCN1 channels. Gabapentin also caused a hyperpolarizing shift in the V1/2 of Ih measured from HCN4-expressing PV+ inhibitory neurons in the spinal dorsal horn. Gabapentin had minimal effect on Ih recorded from CR+ neurons. Consistent with this, immunohistochemical analysis revealed that the majority of CR+ inhibitory neurons do not express somatic HCN4 channels. In conclusion, GBP reduces HCN4 channel-mediated currents through a hyperpolarized shift in the V1/2. The HCN channel subtype selectivity of GBP provides a unique tool for investigating HCN4 channel function in the central nervous system. The HCN4 channel is a candidate molecular target for the acute analgesic and anticonvulsant actions of GBP.